THE HISTORICAL, SCIENTIFIC SIGNIFICANCE OF THE WORK "BABURNAMA" IN YOUTH EDUCATION (Journal of Universal Science Research, 2023)
In this article Zahiriddin Muhammad Babur's greatest work The main topics covered in the work "Boburnoma" are explained from a scientific, historical and educational point of view. The work "Boburnoma" by Zahiriddin Muhammad Babur is noteworthy as a historical literary source because it contains many historical figures, people of literature and art, religious leaders, There is information about branches and princes, beks, amirs and Umars.